Evidence for Water-Borne Transmission of Highly Pathogenic Avian Influenza H5N1 Viruses - Zhang, Hongbo; Yao, Yanfeng; Li, Yan; Chen, Jianjun; Chen, Ze (Frontiers in Microbiology, 2022)
In this study, we isolated 10 H5N1 strains from water samples in Dongting lake and 4 H5N1 strains from lakeside backyard poultry. These isolates belonged to 3 distinct clades (clade 2.3.2, 2.3.4 and 7). Phylogenetic analysis showed diversified in genome constellation. Genetic characteristics of some viruses isolated from water samples were extremely similar to those from lakeside poultry. Pathogenic experiments showed that selected represented isolates in this study were highly pathogenic for SPF chickens, but had a diversified virulence in mice. The results of our study provide evidence that the introduction of poultry H5N1 viruses into wild waterfowls occurred and water body may play important role.